Issues in defective medicinal product litigation - Meagher, Pierce (Trinity College (Dublin, Ireland). School of Law, 2008)
This thesis explores two issues in medicinal product defect litigation. The first issue relates to the difficulty that people have in suing pharmaceutical companies for medicinal product defects. The second issue involves one of the great imponderables of modem product liability law, which is whether product liability law should be based on negligence or strict liability. In determining these two issues, the methodology of research includes examination of national cases and statute law with the aim of determining the effect these forms of law have on the two questions the thesis poses. Because of the lack of cases relating to medicinal product defects in Europe, reference is made to the extensive pharmaceutical case law that has been developed in America. There has been considerable academic research in this area of the law in the United States and the resulting papers have been consulted widely to support tlie analyses contained in the thesis. The first issue relates to the difficulty that people, injured by defective medicinal products, have in taking legal action against pharmaceutical companies. It is found that the sale of goods legislation does not provide a satisfactory redress for consumers who have been injured by medicinal product design defects. A separate consumer sales code is proposed which should only concern itself with repair and replacement of defective products. When medicinal products are not safe, recourse should only be to negligence and strict liability as envisaged under the Liability for Defective Products Act 1991.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin